Change in symptom clusters in head and neck cancer patients undergoing postoperative radiotherapy: A longitudinal study. (August 2018) - Chiang, S.H.; Ho, K.Y.; Wang, S.Y.; Lin, C.C.
Abstract: Purpose: Research on symptom clusters is a newly emerging field in oncology; however, little evidence regarding symptom clusters in head and neck cancer (HNC) is currently available. To clarify this under-researched area, we investigated symptom clusters among patients with HNC treated with surgery and postoperative radiotherapy. We also examined the pattern of symptom clusters throughout the treatment course. Method: A convenience sample of 100 patients with HNC was recruited in the Ear, Nose, and Throat unit of a medical center in Taiwan. Before undergoing postoperative radiotherapy, patients were asked to complete the MD Anderson Symptom Inventory and a demographic sheet. Patients completed the same inventory questionnaire at week 1, 2, 3, 4, 5, and 6 of radiotherapy. Result: Two symptom clusters were observed, and they were stable throughout the course of radiotherapy. Cluster 1, the HNC-specific cluster, comprised the symptoms of pain, dry mouth, lack of appetite, sleep disturbance, fatigue, drowsiness, distress, and sadness. Cluster 2, the gastrointestinal cluster, included nausea, vomiting, numbness, shortness of breath, and difficulty remembering. Conclusion: This study advanced our knowledge of symptom clusters in patients with HNC. The results are expected to contribute to the development of appropriate assessment and nursing interventions targeting multiple symptoms that may coexist in postoperative radiotherapy. Highlights: There are two symptom clusters in patients with head and neck cancer. These symptom clusters are relatively stable throughout postoperative radiotherapy. Information of symptom clusters should be taken into account to devise care plan.